To the lighthouse - Woolf, Virginia, 1882-1941 (Ware : Wordsworth Classics, 1994)
The novel that established Virginia Woolf as a leading writer of the twentieth century, To the Lighthouse is made up of three powerfully charged visions into the life of one family living in a summer house off the rocky coast of Scotland. As time winds its way through their lives, the Ramseys face, alone and simultaneously, the greatest of human challenges and its greatest triumph-the human capacity for change. A moving portrait in miniature of family life, it also has profoundly universal implications, giving language to the silent space that separates people and the space that they transgress to reach each other. There are very few exceptional and miraculous novels that have the power to change their readers forever. To the Lighthouse is one of them.
Keywords: Loss (Psychology) -- Fiction; Lighthouses -- Fiction; Widowers -- Fiction; Skye, Island of (Scotland) -- Fiction; Scotland -- Fiction